Disruption and Recovery of Computing Tasks: Field Study, Analysis, and Directions - Iqbal, Shamsi; Horvitz, Eric (In Proceedings of the SIGCHI Conference on Human Factors in Computing Systems (CHI ’07), 2007)
We report on a field study of the multitasking behavior of computer users focused on the suspension and resumption of tasks. Data was collected with a tool that logged users’ interactions with software applications and their associated windows, as well as incoming instant messaging and email alerts. We describe methods, summarize results, and discuss design guidelines suggested by the findings.